2003
DOI: 10.1002/jsfa.1423
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring of seed composition of prickly pear (Opuntia ficus‐indica L) fruits during maturation period

Abstract: Prickly pear fruit seeds were subjected to a range of chemical analyses during their 15 week maturation period. Seeds contained on average 71.5 g kg −1 dry matter, 61.9 g kg −1 crude oil, 9.4 g kg −1 protein, 507.4 g kg −1 crude fibre, 12.3 g kg −1 ash and 409.0 g kg −1 carbohydrate. The fatty acid composition of prickly pear seed oil consisted of 1.3-1.9 g kg −1 myristic (14:0), 132.1-156.0 g kg −1 g kg −1 arachidic (20:0) and 2.1-3.0 g kg −1 behenic (22:0) acids, which is comparable with that of corn oil. No… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
27
5

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(39 citation statements)
references
References 8 publications
7
27
5
Order By: Relevance
“…The oil content obtained from the 42 cultivars ranged from 4.09% for Corfu to 8.76% for American Giant. Higher oil content values than the present study were reported by CoS skuner and Tekin [32] (6.91%), Salvo et al [21] (9.14%), and Ramadan and Mörsel [12,13] (9.9%). Labuschagne and Hugo [18] obtained slightly lower values ranging from 2.24 to 5.69% for the 11 cultivars they studied.…”
Section: Anova For Cultivars Season and Cultivar â Season Interactioncontrasting
confidence: 65%
See 1 more Smart Citation
“…The oil content obtained from the 42 cultivars ranged from 4.09% for Corfu to 8.76% for American Giant. Higher oil content values than the present study were reported by CoS skuner and Tekin [32] (6.91%), Salvo et al [21] (9.14%), and Ramadan and Mörsel [12,13] (9.9%). Labuschagne and Hugo [18] obtained slightly lower values ranging from 2.24 to 5.69% for the 11 cultivars they studied.…”
Section: Anova For Cultivars Season and Cultivar â Season Interactioncontrasting
confidence: 65%
“…Cultivars recorded an average oil content of 6.36% (Table 3). [31][32][33] Seed oil content from O. ficus-indica (5-14.4%) [19,34] are lower than the seed oil content of mahaleb cherry (18.5%), black thorn (16.5%), cotton seed (15-24%), soybean (17-21%), grape seed (6-20%), and olive (20-25%). These included the same cultivars than in the present study, although cultivated at a different agroecological region in South Africa.…”
Section: Anova For Cultivars Season and Cultivar â Season Interactionmentioning
confidence: 95%
“…The observed difference in the percentage of oleic (16.8%) and palmitic (9.32%) acids could be due to the degree of maturity of the fruit. According to the literature, there is an increase in saturated fatty acid content towards the end of fruit maturation [7]. The high amount of linoleic acid could be a particular feature of Tunisian prickly pear seed oil compared to the Turkish cultivar (57.7-53.8%) [7] and the German cultivar (53.5%) [8].…”
mentioning
confidence: 98%
“…Opuntia ficus-indica seeds were found to contain on average 71.5 g/kg dry matter, 61.9 g/kg crude oil, 9.4 g/kg protein, 507.4 g/kg crude fibre, 12.3 g/kg ash and 409.0 g/kg carbohydrate (Coskuner and Tekin 2003). The fatty acid composition of prickly pear seed oil consisted of 1.3-1.9 g/kg myristic (14:0), 132.1-156.0 g/kg palmitic (16:0), 14.4-18.5 g/kg palmitoleic (16:1), 33.1-47.9 g/kg stearic (18:0), 210.5-256.0 g/kg oleic (18:1), 522.5-577.6 g/kg linoleic (18:2), 2.9-9.7 g/ kg linolenic (18:3), 4.2-6.6 g/kg arachidic (20:0) and 2.1-3.0 g/kg behenic (22:0) acids, which was comparable with that of corn oil.…”
Section: Nutritive/medicinal Propertiesmentioning
confidence: 99%
“…The seeds of prickly pear are also suitable as animal feed (Coskuner and Tekin 2003). Local dairymen assert that nopalito pads are important for good lactation, imparts a better flavour and quality to the milk and enhances better quality for butter.…”
Section: Other Usesmentioning
confidence: 99%